The Role of Studying Abroad in Attitudes towards Immigration: A European Context - Öz, Yakup; Gök, Enes (Journal of International Students, 2021)
International student mobility has been rising as a global phenomenon in the last few decades, while its impact could be various in different contexts. For the European Union (EU), studying in another EU member country could be regarded as an important factor for the solidarity and integrity of the Union. The current study elaborates on the role of studying abroad regarding the attitudes of people toward immigration in the EU. It shows that people who are studying in an EU member country, belonging to higher social classes and from EU15 countries, are more likely to have positive attitudes toward immigration. But after controlling several socio-demographic variables studying abroad still contributes positively to the attitudes of EU citizens toward immigration. Accordingly, current study provides promising pieces of evidence on the social contribution of studying abroad for both future research and policymakers.